Post-Modernism and the Emergence of Alternate History - Atqo Akmal (UIN Imam Bonjol Padang, 2024)
The emergence of post-modernism in the mid-20th century marked a seismic shift in historical knowledge, challenging long-held assumptions about the relationship between language, truth, and reality. This paper explores the profound impact of post-modernism on the discipline of history, focusing on its influence on the concept of alternate history. Post-modernist thought contends that language constructs our understanding of the world rather than merely representing reality, leading to the recognition that there is no single, objective truth in history. The paper delves into the critiques and alternative frameworks notable historians propose within this post-modernist framework. It begins by examining Alun Munslow's concept of